Is Lateral Impingement a Good Predictor of Peritalar Subluxation in Patients with Adult Acquired Flatfoot Deformity?. Issue 4 (22nd October 2020) - Baumfeld, Daniel; Silva, Thiago A.; Li, Shuyuan; Godoy-Santos, Alexandre L.; Lintz, Francois; Mansur, Nacime S.; Dibbern, Kevin N.; Femino, John E.; Netto, Cesar de Cesar
Category: Ankle Arthritis; Ankle; Hindfoot; Other Introduction/Purpose: Sinus tarsi and Subfibular impingement are considered the main causes of lateral foot pain in patients with Adult Acquired Flatfoot Deformity (AAFD). They are considered important markers in the spectrum of progressive peritalar subluxation (PTS) in patients with AAFD. Recent literature has also highlighted the use of the Middle Facet of the subtalar joint as a more accurate indicator of PTS. The objective of this study was to assess the relationship between lateral impingement and middle facet PTS. Our hypotheses were that patients with sinus tarsi and subfibular impingement would demonstrate more severe PTS than patients with no impingement, and that subfibular impingement would represent a better indicator of pronounced deformity when compared to sinus tarsi impingement. Methods: In this retrospective comparative Cohort Study, we included 110 AAFD patients that underwent standing weightbearing CT (WBCT) as a standard baseline assessment of their foot deformity. The presence or absence of sinus tarsi and subfibular impingements, as well as the incongruence angle and percentage of subluxation of the middle facet of the subtalar joint, were manually measured on multiplanar reconstruction (MPR) WBCT images by a blinded fellowship-trained foot and ankle surgeon. Descriptive statistics were used to describe the rate of sinus tarsi and subfibular impingement as well as mean values for middle facet incongruence angle and subluxation. Wilcoxon test was used to compare the values of PTS at the middle facet in patients with or without sins tarsi and subfibular impingement. A partition prediction model was used to assess the values of middle facet PTS that would foresee a higher risk for lateral impingement. P-values <0.05 were considered significant. Results: Seventy-five percent (n=82) of the AAFD patients had sinus tarsi impingement and 64% (n=70) of the AAFD patients had subfibular impingement. The mean value and 95% CI for middle facet incongruence angle and subluxation percentage were respectively 10.5o (CI, 8.7 to 12.2o) and 28.7% (CI, 23.5 to 33.9%). Middle facet subluxation was significantly higher in patients with sinus tarsi and subfibular impingement by respectively 22.6% and 23.9%, both p-values <0.0001. No similar significant differences were observed on incongruence angle measurements. The partition model demonstrated that the middle facet subluxation percentage was the best predictor of both sinus tarsi (R2=0.15) and subfibular impingements (R2=0.17), with 24.9% subluxation representing an important threshold for higher risk of sinus tarsi (90% incidence) and subfibular impingements (84% incidence). Conclusion: Our results showed significantly increased middle facet subluxation in AAFD patients with sinus tarsi and subfibular impingement. Subfibular impingement was less frequent and associated with more pronounced deformity than sinus tarsi impingement. Measurements of the percentage of subluxation of the middle facet were also found to be the best predictor of impingement, with 29.4% representing an important threshold value above which the risks for both sinus tarsi and subfibular impingement were significantly higher. With that in mind, we would recommend close assessment and follow-up of the amount of middle facet subluxation in the decision-making for the treatment of AAFD patients.